Analisis Pengaruh Bahasa Jerman dalam Pembentukan Kata Serumpun Bahasa Indonesia - Irma Liani; Cahaya Mustika; Chairunissa Nasution; Greace Simaremare; Nurul Azizah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study discusses the factors influencing the absorption of vocabulary from German into Indonesian. The research aims to identify and analyze how and why words from German have entered and developed within the Indonesian vocabulary. Using a descriptive qualitative method with a literature review approach, this study examines various written sources that explore the linguistic relationship between the two languages. The findings show that the absorption of German vocabulary into Indonesian is influenced by several key factors, including colonial history and European influence, the development of science and technology, cultural and educational interactions, and the ease of linguistic adaptation. Various terms in administration, science, medicine, engineering, and culture have been borrowed from German into Indonesian. In conclusion, this vocabulary absorption not only enriches the Indonesian language but also reflects the dynamics of the relationship between the two languages in the context of history.